웹툰에서 영화로의 매체전환 성공 사례 연구 - 영화 <신과함께-죄와 벌>을 중심으로 - 박찬익; Park, Chanik ((사)디지털산업정보학회 논문지, 14(2), 2018)
This media conversion in which webtoons are remediated to movies and dramas has taken off since the mid-2000s. Webtoons may be favorable for media conversion into movies and dramas as the story as finished and has proven to be fun with a fixed readership: however, only a small number of webtoon were successful box office hits or received high viewer ratings. Then in 2017, the movie <Along with the God: The Two Worlds> based on the webtoon, succeed in attracting more more then 10 million viewers. In this regard, this study derived the success factors by comparing and analyzing the narrative structure and visual elements of <Along with the God: The Two Worlds>, which was the biggest hit movie, with the original webtoon. The case analysis showed that there are two necessary elements for success: a text configuration of strategy optimized for media conversion, which is based on understanding the different media characteristics of webtoon and movie; and a configuration strategy that exaggerates the personalities of the characters and compresses the story of a webtoon which features various events and many characters in a long series, in consideration of the characteristics of movie which needs to give a big impact in 2 hours.